Validitas dan praktikalitas bahan ajar fisika materi kalor dan teori kinetik gas mengintegrasikan literasi baru dan literasi bencana untuk kelas XI SMA - Hafizah Rahmi Fitri; fatni mufit; asrizal a (Universitas Negeri Padang, 2020)
The 21st century skills in the 4.0 revolution era demanded that students have new literacy and disaster literacy abilities. The solution to overcome these problems is to develop physics teaching materials that integrate new literacy and disasters. The purpose of this study is validity and practicality of the use of teaching materials integrating new literacy and disaster. Step of Research & Development (R&D) conducted until the product limited trial for the students in XI Senior High School. The data obtained in this study are the validation of the physics lecturer at the faculty of Mathematics and Natural Sciences UNP and the practicality of student in XI grade SMA Pembangunan Laboratorium UNP. The instruments used are validation and practicality test sheets. Analysis of the data used is the analysis of validity and practicality analysis. The results of the study showed that validity of teaching materials integrating new literacy and disaster very well with a value of 86. 17. The second result shows that teaching material has an excellent practicality of 88. 96. So, it can be concluded that the physics teaching material is heat material and kinetic theory of gas integrating new literacy and diseaster is valid and practical use for students of class XI Senior High School.